The Criminal Offense of Obstruction of Justice in Corruption Cases and the Urgency of Its Regulation in Indonesia - Alex Sokhian Gea; Ismaidar Ismaidar; Rahmayanti Rahmayanti (Journal of Research in Social Science and Humanities, 2025)
The criminal offense of obstruction of justice, or acts that hinder the judicial process, constitutes a form of crime that can impede law enforcement, particularly in cases of corruption. Although various acts classified as obstruction of justice have been regulated separately in several Indonesian laws and regulations, such as the Criminal Code (KUHP), Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on the Eradication of Corruption, and Law Number 8 of 1981 on Criminal Procedure, these regulations remain partial and have not provided comprehensive legal certainty. This study aims to analyze the regulation of the criminal offense of obstruction of justice in the context of corruption cases and to examine the urgency of establishing more explicit and integrated regulations in Indonesia. The research method employed is normative juridical research using statutory and conceptual approaches. The results of the analysis indicate that the absence of explicit norms regulating obstruction of justice in corruption cases creates obstacles to law enforcement, particularly against parties who attempt to hinder the investigation, prosecution, and examination of corruption cases. Therefore, legal reform is necessary to clarify provisions concerning obstruction of justice within the Indonesian criminal law system in order to support the effectiveness of corruption eradication efforts and to maintain the integrity of the judicial process.